A Phase II Study of Induction Chemotherapy Followed by Thoracic Radiotherapy and Erlotinib in Poor-Risk Stage III Non–Small-Cell Lung Cancer. Issue 1 (January 2015) - Lilenbaum, Rogerio; Samuels, Michael; Wang, Xiaofei; Kong, Feng Ming; Jänne, Pasi A.; Masters, Gregory; Katragadda, Sreedhar; Hodgson, Lydia; Bogart, Jeffrey; Bradley, Jeffrey; Vokes, Everett
<x xml:space="preserve">Abstract</x> Introduction: Patients with stage III non–small-cell lung cancer and poor performance status and/or weight loss do not seem to benefit from standard therapy. Based on the preclinical interaction between epidermal growth factor receptor inhibitors and radiation, we designed a trial of induction chemotherapy followed by thoracic radiotherapy and concurrent erlotinib. Methods: Patients with poor-risk unresectable stage III non–small-cell lung cancer received two cycles of carboplatin at an AUC of 5 and nab-paclitaxel at 100 mg/m2 on days 1 and 8 every 21 days, followed by erlotinib administered concurrently with thoracic radiotherapy. Maintenance was not permitted. Molecular analysis was performed in available specimens. Seventy-two eligible patients were required to test whether the 1-year survival rate was less than 50% or greater than or equal to 65% with approximately 90% power at a significance level of 0.10. Results: From March 2008 to October 2011, 78 patients were enrolled, three of whom were ineligible. The median age was 68 (range, 39–88) and 32% were aged greater than or equal to 75 years. Patients were evenly distributed between stages IIIA and IIIB and the majority had performance status 2. The overall response rate was 67% and the disease control rate was 93%. Treatment was well tolerated. The median PFS and OS were 11 and 17 months, respectively. The overall 12-month OS was 57%, which narrowly missed the prespecified target for significance. Conclusions: Patients with poor-risk stage III non–small-cell lung cancer had better than expected outcomes with a regimen of induction carboplatin/nab-paclitaxel followed by thoracic radiotherapy and erlotinib. However, as per the statistical design, the 12-month OS was not sufficiently high to warrant further studies.